Success Rates of Endoscopic-Assisted Probing Compared to Conventional Probing in Children 48 Months or Older - Galindo-Ferreiro, Alicia; Khandekar, Rajiv; Akaishi, Patricia Mitiko; Cruz, Augusto; Gálvez-Ruiz, Alberto; Dolmetsch, Angela; Schellini, Silvana [UNESP] (Taylor & Francis, 2018)
Background: To evaluate the success rates of endoscopic-assisted probing compared to conventional probing in children 48 months or older. Methods: This retrospective study included children 48 months and older with CNLDO who underwent endoscopic-assisted probing or conventional probing between January 2011 to August 2015 at a tertiary eye care hospital in central Saudi Arabia. Probing was considered successful when signals of tearing or discharge disappeared and fluorescein dye disappearance test (FDDT) was normal. Demographic data, clinical features, intraoperative and postoperative variables were correlated to the success rate. Results: One hundred and twelve children with CNLDO undergoing endoscopic-assisted (37 patients) or conventional (75 patients) probing were included. The success rates of endoscopic-assisted and conventional probing were 94.6% [95% confidence interval (CI): 89.5–99.7] and 58.7% [95% (CI): 47.6–69.8], respectively. The success rate was higher with endoscopic probing, especially in older children. Conclusions: Endoscopic-assisted probing can achieve better outcomes to treat CNLDO, even in older children. The significantly higher success rates with endoscopic probing are likely due to the ability to observe and treat associated problems.
Keywords: Congenital disorders; lacrimal disease; lacrimal disorders; nasolacrimal duct; surgery